Expression correlates between Annexin A1 and A2 autoantibodies in patients with Behçet's disease. Issue 1 (19th January 2018) - Hussain, Muhammad; Chen, Peng; Mei, Guang; Li, Yongzhe; Du, Hongwu
Abstract : The autoantibodies profile of Behçet's disease (BD) is yet incompletely understood. Annexins are a family of highly conserved proteins which are involved in some human autoimmune diseases. Autoantibodies directed toward Annexin A1 and A2 are involved in BD pathology, but correlation in their clinical role is controversial. The aim of our study is to estimate and evaluate the expression correlation between Annexin A1 and A2 autoantibodies in BD patients. We have designed and implemented different technical approaches to prove the hypothesis. First, bioinformatics tools such as amino acid sequence alignment, epitope prediction analysis, and 3D structural comparison were performed to find out the correlation between Annexin A1 and A2. Second, amplification of the corresponding gene by RT-PCR, then cloning, and purification techniques were applied to acquire the recombinant Annexin A1. Third, the target protein band was excised from gel electrophoresis, digested with trypsin, and analyzed by MALDI-TOF/TOF. Finally, in-house ELISA was developed to determine the induced anti-Annexin A1 autoantibodies in BD patients. Obtained results demonstrated that the BD serum reactivity against recombinant Annexin A1 was significantly higher as compared with healthy control (HC) ( P <0.001). Moreover, bioassay results of Annexin A1 and A2 also showed the presence, absence, and independent coexistence of autoantibodies, when reacted with BD sera. In conclusion, Annexin A1 has a similar immunogenic expression and correlation with its analog Annexin A2 and their association may be a novel immune target of BD in Han Chinese population.